The Impact of Liquidity, Solvency, and Efficiency on Profit Growth in Indonesian Automotive Companies (2017-2021) - Grace; Nanik Sisharini; Lily Kustiani; Moh Burhan; Boge Triatmanto (Jurnal Penelitian, 2025)
This study aims to determine and analyze the influence Current Ratio, Debt to Equity Ratio and Total Assets Turnover on profit growth in automotive companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study used a population of 14 automotive companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling technique and obtained a sample of 10 automotive companies that had met the sample criteria. The data analysis techniques used were descriptive statistics, classical assumptions (normality test, multicollinearity test, autocorrelation test and heteroscedasticity test), multiple linear regression analysis, hypothesis test and coefficient of determination. Simultaneous results show that Current Ratio, Debt to Equity Ratio and Total Assets Turnover has a significant effect on profit growth. The results of the partial test show that Current Ratio has a negative and insignificant effect on profit growth. Debt to Equity Ratio has a significant negative effect on profit growth. Total Assets Turnover has a positive and insignificant effect on profit growth.